2019
DOI: 10.4149/neo_2018_181020n786
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key pathways and genes changes in pancreatic cancer cells (BXPC-3) after cross-talk with primary pancreatic stellate cells using bioinformatics analysis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant tumors with poor prognosis, and the interaction between activated pancreatic stellate cells (PSCs) and PDAC cells plays an important role in the development of PDAC. The aim of this study was to identify gene changes in BXPC-3 after cross-talk with PSCs and reveal their potential mechanisms. The gene expression profiling analysis of BXPC-3 was completed after co-culture with primary PSCs for 48 h. The gene ontology (GO) and Kyoto Encyclopedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…This study may assist clinicians to choose targets for immunotherapy and make personalized treatment strategy for pancreatic cancer. Tang et al (63) reported that OAS1 and OAS3 are key gene changes in pancreatic cancer cells (BXPC-3) compared with primary pancreatic stellate cells using bioinformatics analysis. Glaß et al (64) showed that OASL is a driver and therapeutic target candidate in pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This study may assist clinicians to choose targets for immunotherapy and make personalized treatment strategy for pancreatic cancer. Tang et al (63) reported that OAS1 and OAS3 are key gene changes in pancreatic cancer cells (BXPC-3) compared with primary pancreatic stellate cells using bioinformatics analysis. Glaß et al (64) showed that OASL is a driver and therapeutic target candidate in pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Robert et al indicated that OAS1 expression was correlated with azacytidine (AZA) sensitivity in the NCI-60 tumor cell lines and was a biomarker for predicting AZA sensitivity of tumor cells (Banerjee et al, 2019). Besides, one gene expression profiling combining bioinformatics analysis in regard to PAAD identified that OAS1 was related to worse prognosis of PAAD (Tang et al, 2019). A basic experiment showed that pancreatic cancer cell lines with high OAS expression were resistant to oncolytic virus therapy (Moerdyk-Schauwecker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are three types of OAS proteins in humans, OAS1, OAS2 and OAS3. OAS1 has been demonstrated to be associated with pancreatic cancer and prostate cancer ( 41 , 45 ). Oncolytic virus therapy is a promising treatment option for pancreatic cancer; however, high expression levels of OAS in cell lines are associated with resistance to this therapy ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the following four genes provides guidance for searching for targeted genes for immunotherapy of pancreatic cancer. It has been reported that immune response by four IRGs (OAS1, MET, IL1R2 and IL20RB) is associated with the prognosis of pancreatic cancer (39)(40)(41)(42). The OAS system is an antiviral signaling pathway induced by interferon and OAS genes that are described as interferon-stimulated genes (43,44).…”
Section: Discussionmentioning
confidence: 99%